(untitled) (Książnica Śląska, 2025)
„Zaranie Śląskie” was the first literary magazine in Silesia. It was released alternately in Cieszyn and Katowice, since 1907. For researchers interested in literary life in the interwar period, it is today the most valuable source of information and a document of the literary aspirations of the region, revealing everything weak but also exceptional in it. The article recalls the genesis of the quarterly and draws special attention to its functioning in the years 1929–1939. The author devoted a significant amount of space to the co-creators of the magazine, evoking the virtues of, among others, Ernest Farnik, Julian Przyboś, Kornel Filipowicz, and Gustaw Morcinek.